Interpersonal Conflict and Knowledge Hiding Behavior: Mediating Role of Perceived Competition - Joko Prayetno; Muhammad Rasyid Abdillah (SAINS ORGANISASI, 2022)
The background of this research is based on the importance of measuring the conflicts that occur in a company that caused knowledge hiding behavior. The purpose of this study was to determine the extent of the relationship between interpersonal conflict and knowledge hiding behavior by mediating perceived competition. By using samples from pharmaceutical companies, there are often visible or invisible interpersonal conflicts that caused subordinates to engage in knowledge hiding behavior. Furthermore, perceived competition also mediates the psychological process underlying the link between interpersonal conflict and knowledge hiding behavior. With the results of the existing research, it is hoped that it will become a picture for supervisors to prevent counterproductive knowledge behavior, such as knowledge hiding through reducing the intensity of the interpersonal conflict.